Subjective assessment of adhesives usage by complete denture wearers in a brazilian population - Pero, Ana Carolina [UNESP]; Paleari, André Gustavo [UNESP]; Rodriguez, Larissa Santana [UNESP]; Leite, Andressa Rosa Perin [UNESP]; Roccia, Andreia Alonso [UNESP]; Compagnoni, Marco Antonio [UNESP] (My University, 2012)
The information about the knowledge and usage of denture adhesives is still limited, particularly in Brazilian populations. Objective: The purpose of this study was to investigate the aspects related to the use or nonuse of denture adhesives by complete denture wearers. Material and method: Questionnaires were applied to 100 bimaxillary complete denture wearers concerning their usage of denture adhesives. The survey was carried out according to three categories: those who had never tried adhesive, those who had tried adhesive at least once but no longer used it, and those who currently used it. Result: Of the 100 participants, 80% had never tried adhesives, 16% had tried at least once but no longer used it and 4% had used on a regular basis. Conclusion: Within the limitations of this study, the results of this subjective assessment suggest that within the participants that had never tried adhesives, 77.5% inform that the adhesive is not needed, and all participants who regularly use it inform its efficiency.

Estudos subjetivos sobre o conhecimento e uso de adesivos para prótese ainda é limitado, especialmente em populações brasileiras. Objetivo: O objetivo deste estudo foi investigar os aspectos relacionados ao uso ou não de adesivos para prótese por usuários de próteses totais. Material e método: Foram aplicados a 100 usuários de próteses totais bimaxilares questionários relativos à utilização de adesivos para prótese. A pesquisa foi realizada de acordo com três categorias: aqueles que nunca tinham experimentado o adesivo, aqueles que já tinham utilizado o adesivo pelo menos uma vez e que já não utilizavam mais, e aqueles que utilizam regularmente. Resultado: Dos 100 participantes, 80% nunca haviam utilizados adesivos, 16% já haviam experimentado pelo menos uma vez, mas já não utilizavam mais e 4% utilizavam regularmente. Conclusão: Dentro das limitações deste estudo, os resultados desta avaliação subjetiva sugere que entre os participantes que nunca haviam experimentado adesivos, 77,5% informaram que o adesivo não era necessário, e todos os participantes que utilizam regularmente informaram a sua eficiência.
Avaliação subjetiva do uso de adesivos por portadores de próteses totais bimaxilares em uma população brasileira
Keywords: Denture; Complete; Adhesives; Questionnaires; Prótese total; Adesivos; Questionários